Clinical Legal Education in the Legal Aid Institution - Ulfah, Maria (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical legal education in a Faculty of Law can be done through thecurriculum or ongoing regular activities outside the curriculum. Manycampuses have implemented clinical legal education in the compulsorycourses or elective courses. It would be good if the clinical legaleducation has been implemented in the course of one eye, but thesetting of clinical legal education in a college course for which has notbeen set is not easy to do. Difficulty setting of clinical legal education inthe subjects did not dampen interest in developing clinical legaleducation on the campus. Faculty of Law, Universitas KatolikParahyangan (UNPAR) develop it through ongoing routine activitiesincluded in the "Pengayoman" Legal Aid Institution (Pengayoman).Various activities in Pengayoman intended to achieve communityservice in the field of law committed by the students and faculty forapproximately. This paper intended to deliver an analysis of activitiesorganized by Pengayoman with clinical legal education that stems fromthe United States, known in Asia, and growing in Indonesia. The analysisalso endeavour to identify a variety of benefits and barriers to clinicallegal education through outside the curriculum of the Law Faculty. Thispaper opens with input for clinical legal education more leverage andmore innovative.